Malaria entre la población Tule (Kuna) del resguardo Caimán Nuevo (Turbo y Necoclí; Antioquia, Colombia), 2003-2004 (2005)
ABSTRACT: To study the annual incidence or malaria in 2001-2003 among the Tules of Resguardo Caimán Nuevo. Methodology: a descriptive study: a) retrospective: with data search in hospital records of Turbo and Necocli Hospitals and the Local Health Center at the Resguardo; b) prospective: to measure malaria prevalence by thick smear. Results: A) Malaria incidence during 2001-2003 according to our patients records. The annual index, per 1000 exposed was 154,67 in 2001, 146,89 in 2002 y 601,17 in 2003. B) According to records at the Resguardo Local Health Center a mean number of a positive thick smear was found in 39,4%. C) Malaria prevalence after active search was 433 (7,16% positive). The mean P. falciparum parasitaemia was 993 parasites/ μL (SD= 678). A 13% had history of malaria during the past month and 31% during the past year. Of all adult women, 41% had history of malaria during a pregnancy, a 76% of the population uses traditional medicine to prevent malaria. Each malaria case resulted in a loss of 7 working days.